Improving Students’ Vocabulary by Exploring Rarely Discussed Aspects of Vocabulary Growth - Masyudi, Masyudi; Yunike, Yunike (Lembaga Publikasi Ilmiah Dwipantara, 2025)
Vocabulary acquisition is a fundamental aspect of language learning that significantly influences students’ communication skills and academic performance. However, traditional vocabulary teaching methods often emphasize rote memorization and word lists, neglecting less commonly explored strategies that can enhance vocabulary growth more effectively. This study examines the impact of integrating rarely discussed aspects of vocabulary development, such as lexical chunks, morphological awareness, etymology, and contextual learning, on second-grade senior high school students. The research employs a qualitative and quantitative approach, incorporating classroom observations, student assessments, and teacher feedback to analyze the effectiveness of these strategies. Findings indicate that students exposed to these methods show a deeper understanding of word formation, improved retention, and greater confidence in using new vocabulary in different contexts. Additionally, engaging students in interactive learning activities, such as word mapping, etymological exploration, and phrase-based instruction, fosters a more meaningful and long-term vocabulary acquisition process. By shifting the focus from isolated word memorization to a more holistic and contextualized approach, this study provides valuable insights for educators aiming to enhance students' vocabulary proficiency. The findings suggest that incorporating innovative vocabulary learning strategies into English language teaching can create a more dynamic and effective learning environment for senior high school students.